A new look at the drama of the 20th century (Филологический класс, 2009)
The author reviews one of the recent works devoted to the drama, in particular, problems of expression of the author's consciousness in the drama, points to the efficiency of allocation of the three major trends in 20th century drama and presentation of material on the panoramic principle.